"Role Of Sustainable Practices In Promoting Environmentally Responsible Tourism: A Mediation Analysis" (International Journal of Environmental Sciences, 2025)
This study explores the connection between tourism involvement and sustainable practices toward eco-tourism, aiming to understand how these practices influence the adoption of sustainable tourism development within Rajasthan’s tourism sector. A comprehensive analytical framework is constructed and tested using primary data gathered from eco-tourists, local residents, and key stakeholders in the tourism industry. Structural Equation Modelling (SEM) is applied to test the proposed hypotheses and examine the relationships among core variables. The findings indicate that sustainable practices have a direct and significant effect on sustainable tourism development. However, tourism involvement does not mediate the link between sustainable practices and sustainable tourism outcomes, suggesting that the implementation of sustainable practices independently drives positive sustainability impacts. By concentrating on the distinctive eco-tourism environment of Rajasthan, the study offers meaningful insights into sustainability mechanisms within tourism. The findings highlight the need for tourism operators and policymakers to enhance eco-tourism awareness and education initiatives, thereby fostering environmentally responsible behavior and greater engagement. Furthermore, tourism managers are encouraged to embed sustainable practices—such as conserving natural resources and preserving cultural heritage—into their operational models and promotional efforts.